PENGARUH LATIHAN LARI ZIG-ZAG TERHADAP KEMAMPUAN MENGGIRING DALAM PERMAINAN SEPAK BOLA PEMAIN SSB DEKATE FC - Ramadhany, M Rendy Dwi; Anwar, Khoirul; Hidayatullah, Fajar (Fakultas Ilmu Keolahragaan Unimed, 2024)
So many students who like soccer makes soccer always crowded among school students. However, there are a number of things that students need to know and master before playing soccer, namely kicking techniques, control/stopping techniques, dribbling techniques, heading techniques, grabbing techniques and throw-in techniques. One of the most important techniques is the herding technique. In the dribbling technique itself, expertise is needed so that you can dribble by deceiving your opponent, namely by using a zig-zag run. This study used a quasi-experimental research method using the SPSS trial, namely the homogeneity test, the normality test and the simple paired t-test. The research obtained satisfactory results, one example is the simple paired t-test obtained a value of 0.005 which means that there is a difference in the results of the tests that have been carried out